Paradoxes and problems in the causal interpretation of equilibrium economics - Keshav Dogra (Federal Reserve Bank of New York, 2024)
Equilibrium assumptions posit relations between different people's beliefs and behavior without describing a process that causes these relations to hold. I show that because equilibrium models do not describe a causal process whereby one endogenous variable affects another, attempts to decompose the effects of shocks into "direct" and "indirect" effects can suggest misleading predictions about how these models work. Equilibrium assumptions also imply absurd paradoxes: history can determine future behavior without affecting any intervening state variables today; individuals can learn information that no one originally possesses by observing each other's actions. This makes equilibrium models unreliable tools to study how economic systems coordinate activity and aggregate dispersed information. I describe how to construct non-equilibrium models that avoid these paradoxes and can be interpreted causally.
Keywords: B41; C70; D50; D83; E70; 330; equilibrium; disequilibrium; mechanisms; causality; paradoxes